Diabetes Remains the Number One Diagnosis Among Patients Visiting Nephrology Clinic - Tarif, Nauman (Pakistan Journal of Kidney Diseases, 2024)
There is a huge burden of kidney disease overloading the hospitals and nephrology clinics. No clear data exists as to what kind of patients are visiting the outpatient departments. Pakistan is seeing a huge load of diabetics and naturally a significant portion of diabetics ultimately develop diabetic kidney disease. It is important to document such stats so as to make a concrete strategies for preventive medicine. True big data is difficult to obtain due to to the obvious hurdles in manpower and lack of interest of almost all quarters to document the true prevalence of noncommunicable diseases. This study highlights the clinical diagnoses of patients presenting to a private nephrology clinic.